2017
DOI: 10.18632/oncotarget.23818
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning improves myocardial parameters and clinical outcomes during primary percutaneous coronary intervention: a meta-analysis of randomized controlled trials

Abstract: We conducted a systematic review and meta-analysis to evaluate the effects of remote ischemic conditioning on myocardial parameters and clinical outcomes in ST segment elevation acute myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention. Ten eligible randomized controlled trials with 1006 STEMI patients were identified. Compared with controls, remote ischemic conditioning reduced the myocardial enzyme levels (standardized mean difference =-0.86; 95% CI: -1.44 to -0.28; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Looking at the current scenario, there are only a few available intervention strategies for protecting the heart and brain from ischemia-reperfusion injury due to insufficient clinical trial data and lack of pharmacokinetic and pharmacodynamic study [38]. Again, the complex sequential events leading to this condition also limit the benefits of different surgical interventions like coronary artery bypass graft surgery and percutaneous coronary intervention [39].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Looking at the current scenario, there are only a few available intervention strategies for protecting the heart and brain from ischemia-reperfusion injury due to insufficient clinical trial data and lack of pharmacokinetic and pharmacodynamic study [38]. Again, the complex sequential events leading to this condition also limit the benefits of different surgical interventions like coronary artery bypass graft surgery and percutaneous coronary intervention [39].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…A total of 1037 potential records were searched from the databases. After screening and reviewing, seven studies were included for further evaluation (Bøtker et al, 2010;Hausenloy et al, 2019;Liu et al, 2018;Munk et al, 2010;Prunier et al, 2014;Sloth et al, 2014;Yamanaka et al, 2015). These studies included a total of 2796 patients in RIC-pre group and 2818 patients in control group, as described in Fig.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Among these included studies, three were from the same clinical randomized trial (NCT00435266) with different reported endpoints (Bøtker et al, 2010;Munk et al, 2010;Sloth et al, 2017). Three studies revealed long-term clinical adverse events (Hausenloy et al, 2019;Liu et al, 2018;Sloth et al, 2014), and three studies reported short-term clinical outcomes (Bøtker et al, 2010;Hausenloy et al, 2019;Yamanaka et al, 2015). In contrast to other included RCTs, two RCTs by Yamanaka and Hausenloy were single-blinded (Hausenloy et al, 2019;Yamanaka et al, 2015), and RIC-pre protocols were performed by an automated continuous blood-pressure monitoring device.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Meta-analyses of clinical trials point towards an association between RIC and lower levels of cardiospecific biomarker release, and suggest a beneficial effect of RIC on major adverse cardiac events such as mortality, myocardial infarction (MI), and congestive heart failure (CHF) combined or separately. [7][8][9][10][11][12] A trend towards reduced clinical events at follow-up after RIC in ST-elevation myocardial infarction (STEMI) patients has been reported in two trials 13,14 while no improvement by RIC was reported in one recent large multicenter trial 15 providing additional clinical data.…”
Section: Introductionmentioning
confidence: 99%